Manajemen Strategik Pesantren di Era Digital: Menjembatani Tradisi Keilmuan dan Inovasi Teknologi - Abrar, Muhammad Thoiful; Saputra, Yusril Ihza; Kamil, Moh.; Rohman, Muhammad Kholilur; Holidi, Moh.; Muhlas, Moh.; Mudarris, Badrul (Jurnal Manajemen dan Ilmu Administrasi, 2025)
The purpose of this study is to gain a better understanding of how Islamic boarding schools (Pesantren) can implement strategic management in the modern era while maintaining the values ​​of Islamic academic tradition. This study focuses on MA Nurul Islam Ganding Sumenep, which seeks to incorporate digital systems into its management while maintaining the characteristics of an Islamic boarding school. This research was conducted qualitatively through a case study. After being collected through field observations, interviews, and document reviews, data were analyzed through the steps of data condensation, presentation, and verification using an interpretive approach. The results show that Islamic boarding schools can balance tradition with innovation by using three main strategies: incorporating traditional values ​​into digital planning, changing leadership styles to an adaptive and collaborative model, and improving human resources to address digital challenges. This process demonstrates that modernizing Islamic boarding schools does not mean abandoning Islamic values, but rather using technology to expand them. This study demonstrates that values-based strategic management also known as value-based strategic management can connect spirituality, culture, and technological advancements to keep Islamic boarding schools relevant, superior, and competitive in the digital era